Loving Texts Two at a Time : The Film Remake - Quaresima, Leonardo (Cinémas)

(untitled) (Cinémas, 2002)
AbstractThis article seeks to illustrate, first of all, how little interest film theory has shown in the notion of the remake. Beginning with a discussion of the principal definitions of the remake and its principal varieties, the author isolates some of the most characteristic practices in the process of remaking. The article draws particular attention to the ways in which the remake alters the original text.